2016
DOI: 10.1007/s10597-015-9936-7
|View full text |Cite
|
Sign up to set email alerts
|

Client, Contextual and Program Elements Influencing Supported Employment: A Literature Review

Abstract: Supported employment is an evidence-based practice with a well-established research base. Most studies track such outcomes as employment rates, time to employment and wages earned. Few studies address client and contextual factors that impact outcomes or consider program elements beyond those that comprise the individual placement and support model. This paper reviews existing literature to shed light on the following questions: (1) What impact do labour market trends have on the effectiveness of SE? (2) How l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 102 publications
(108 reference statements)
1
17
0
3
Order By: Relevance
“…Non significance maybe due to missing data (8%) [ 55 ], resulting from the difficulty rating the variable. Additionally, therapists involved in this present study concurred with other authors [ 34 , 70 , 71 ] that the environmental factors are clinically important. The final multiple logistic regression model included Adapts Routines to Minimize Difficulties and Work-related Goals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Non significance maybe due to missing data (8%) [ 55 ], resulting from the difficulty rating the variable. Additionally, therapists involved in this present study concurred with other authors [ 34 , 70 , 71 ] that the environmental factors are clinically important. The final multiple logistic regression model included Adapts Routines to Minimize Difficulties and Work-related Goals.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies have found active, positive symptoms are associated with failure to attain employment [ 22 , 23 ] or loss of employment [ 24 ]; while others, including a meta-analysis [ 15 ], have found no association. Psychosocial variables such as a strong work ethic [ 25 27 ], expressed desire to work [ 28 30 ], maintain habits [ 19 , 31 ] and self-esteem, self-efficacy [ 19 , 32 34 ] and work history [ 15 , 35 ] have also been investigated and identified as predictive of success in return to employment or education.…”
Section: Introductionmentioning
confidence: 99%
“…Peer Support/Social Support Peer support may be helpful for dealing with work issues and maintaining employment, although the research is limited (68). Qualitative studies have highlighted the importance of peer and community supports for employees with severe mental illness, including friends, and peers from vocational groups, mental health groups, or spiritual groups (63).…”
Section: Other Supports For Sustaining Employmentmentioning
confidence: 99%
“…Our concern echoes the statement by Kirsh in an earlier review paper on client factors and contextual factors as predictors of SE program success who stated that "… the literature indicates that SE outcomes are dependent on labour market trends, yet little has been done to adapt SE to difficult economic times." 71 . From our perspective, it is not only the difficult economic times that SE needs to adapt to but more so to a long-term structural change in the labour market.…”
Section: Resultsmentioning
confidence: 99%